COMMUNICATIONAL ASPECTS IN HEALTH CARE (Fiep Bulletin - online, 2013)
Interpersonal communication is a human means of interaction, exchange and transmission of meanings. Starting from this principle, this study aimed at understanding communicational aspects involved in the interaction between the professional and the patient with HIV/Aids at a state health service in Natal, Brazil. It is a qualitative study, performed by interviewing 22 professionals. The textual data of the interviews were analyzed by ALCESTE software. Analysis points to a predominantly female profile, age group between 40 and 50 years, married, university-educated, a larger number of physicians and a mean length of service of 10 years. The textual material was divided into five thematic classes for analysis. The professionals considered verbal communication fundamental for the patient to understand information and orientations, thus adhering to the treatment. Interaction is conceived as a more technical-communicative skill than a subjective ability. The health service activities are directed toward individualized actions, with an emphasis on treatment. Medicalization is the daily focus. The professionals refer to the disorganization of the service, a place without coordination or interdisciplinary actions. Communication occurs as the instrumentalization of the technical, reflecting a service centered on the curative, on medical attention, and on the individual, deprived of communicative interaction. Each thematic class had the significant contribution of discourses representative of all the professional categories, with the exception of the physician. By way of concluding “representative discourse” is associated to a remarkable and significant positioning to constructing the context. Questions are raised to encourage the rethinking of the communicative and interactive practices of professionals in the health area, mainly those of the physician related to care, since clinical knowledge comes from the communicative practice of listening to the discourse of the Other.
Keywords: Communication; Interaction.; Professional-patient